2004
DOI: 10.1074/jbc.m410379200
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreatic Duodenal Homeobox-1 Protein (Pdx-1) Interacts with Histone Deacetylases Hdac-1 and Hdac-2 on Low Levels of Glucose

Abstract: We have previously demonstrated that high concentrations of glucose stimulate insulin gene expression by causing hyperacetylation of histone H4 at the insulin gene promoter. Furthermore, we have shown that the glucose-mediated hyperacetylation of histone H4 depends on the recruitment of the histone acetyltransferase p300 by the beta cell-specific transcription factor Pdx-1. In this study, we demonstrate that the histone deacetylases Hdac-1 and Hdac-2 are rapidly recruited to the insulin promoter in the mouse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 47 publications
4
73
0
1
Order By: Relevance
“…It has been previously demonstrated that PDX1 specifically binds the proximal insulin promoter of MIN6 cells by a ChIP assay (47). 48 h following PDX1-siRNA treatment, we observed an 80% reduction in PDX1 occupancy at the insulin II promoter in MIN6 cells (Fig.…”
Section: Sox6 Negatively Regulates Transcripts Of Genes For Insulin Amentioning
confidence: 65%
“…It has been previously demonstrated that PDX1 specifically binds the proximal insulin promoter of MIN6 cells by a ChIP assay (47). 48 h following PDX1-siRNA treatment, we observed an 80% reduction in PDX1 occupancy at the insulin II promoter in MIN6 cells (Fig.…”
Section: Sox6 Negatively Regulates Transcripts Of Genes For Insulin Amentioning
confidence: 65%
“…These events appear to be necessary for preproinsulin transcription induced by glucose (96-100). Conversely, at low glucose levels where insulin production is shut off, the acetylation of histone H4 at the insulin promoter is abolished, correlating with recruitment of HDAC1 and -2 to the in- sulin promoter by Pdx1 (97,101). NeuroD1 also interacts with p300 and is acetylated by the p300-associated factor (PCAF).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Apart from interaction with transcription factors, Pdx1 also appears to recruit transcriptional co-activators (proteins that bridge Pdx1 to the basal transcriptional machinery), including CBP/ p300 [68,113,141,145,146], Set7/9 [147], Bridge-1 [148], PCIF1 [149], and histone deacetylases (HDACs) [150]. Once recruited, cofactors are believed to serve as a physical or functional "bridge" that allows Pdx1 to communicate with components of the basal transcriptional machinery.…”
Section: Mechanisms Of Transcriptional Regulation By Pdx1mentioning
confidence: 99%